Reform of the New Criminal Procedure Code and the Challenges of Strengthening the Role of Advocates in Indonesia’s Criminal Justice System - Chitto Cumbhadrika; Muchlas Rowi (Federalisme: Jurnal Kajian Hukum dan Ilmu Komunikasi, 2026)
The reform of the Criminal Procedure Code (KUHAP) introduces new regulations regarding the position of advocates as law enforcers through Article 149, which includes the recognition and protection of professional immunity. It is seen as a progressive step in strengthening the role of advocates in the criminal justice system. However, the formulation of norms requiring the implementation of duties "in good faith" raises legal issues because it is not accompanied by clear and measurable parameters. The ambiguity has the potential to give rise to multiple interpretations and open a void for the criminalization of advocates through restrictive interpretations by law enforcement officials. This study aims to analyze the normative construction of Article 149, test its consistency with Law Number 18 of 2003 concerning Advocates, and assess its conformity with the principles of legal certainty and the guarantee of the right to legal aid in the 1945 Constitution of the Republic of Indonesia. The research method employed is normative legal research combining statutory, conceptual, and comparative approaches. The analysis is conducted through grammatical, systematic, and teleological interpretations of the relevant norms. The study shows that Article 149 provides symbolic reinforcement of the advocate's position, but does not thoroughly provide legal certainty due to the lack of objective parameters regarding good faith and the potential for horizontal disharmony with the immunity provisions in the Advocates Law. Normative strengthening requires regulatory harmonization and the formulation of clear operational standards to guarantee professional independence while maintaining accountability.